In vitro study of radiosensitivity in colorectal cancer cell lines associated with Lynch syndrome - Sun, Mingzhu; Moquet, Jayne; Barnard, Stephen; Mancey, Hannah; Burling, David; Baldwin-Cleland, Rachel; Monahan, Kevin; Latchford, Andrew; Lloyd, David; Bouffler, Simon; Badie, Christophe; Anyamene, Nicola A.; et al. (Frontiers in Public Health, 2024)
Lynch syndrome patients have an inherited predisposition to cancer due to a deficiency in DNA mismatch repair (MMR) genes which could lead to a higher risk of developing cancer if exposed to ionising radiation. This pilot study aims to reveal the association between MMR deficiency and radiosensitivity at both a CT relevant low dose (20 mGy) and a therapeutic higher dose (2 Gy). Human colorectal cancer cell lines with (dMMR) or without MMR deficiency (pMMR) were analysed before and after exposure to radiation using cellular and cytogenetic analyses i.e. clonogenic assay to determine cell reproductive death; sister chromatid exchange (SCE) assay to detect the exchange of DNA between sister chromatids; γH2AX assay to analyse DNA damage repair; and apoptosis analysis to compare cell death response. The advantages and limitations of these assays were assessed in vitro, and their applicability and feasibility investigated for their potential to be used for clinical samples. Results from the clonogenic assay indicated that the pMMR cell line (HT29) was significantly more radio-resistant than the dMMR cell lines (HCT116, SW48, and LoVo) after 2 Gy X-irradiation. Both cell type and radiation dose had a significant effect on the yield of SCEs/chromosome. When the yield of SCEs/chromosome for the irradiated samples ( 2Gy) was normalised against the controls, no significant difference was observed between the cell lines. For the γH2AX assay, 0, 20 mGy and 2 Gy were examined at post-exposure time points of 30 minutes (min), 4 and 24 hours (h). Statistical analysis revealed that HT29 was only significantly more radio-resistant than the MLH1-deficient cells lines, but not the MSH2deficient cell line. Apoptosis analysis (4 Gy) revealed that HT29 was significantly more radio-resistant than HCT116 albeit with very few apoptotic cells observed. Overall, this study showed radio-resistance of the MMR proficient cell line in some assays, but not in the others. All methods used within this study have been validated; however, due to the limitations associated with cancer cell lines, the next step will be to use these assays in clinical samples for the understanding of the biological and mechanistic effects of radiation in Lynch patients.